KAITAN ANTARA PERSEPSI PESERTA TERHADAP PASAR LELANG DENGAN SIKAP PESERTA PASAR LELANG AGROFORWARD DI PROVINSI JAMBI - Nida Kemala; Siti Abir Wulandari (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
The  research  was  applied   in  the  Agroforward  Auction  Market  that conducted at Jambi Province. It was held in order to find the description of  some variables  i.e. the perception of the market participants  and their attitude toward  to this market system.The  snow  ball  sampling  technic  was  applied  to  find  25  samples  and  it is  completed by applying the Chi-Square Test as analysis instrument in this research.The  result  of  the  research  showed  that this  market  participants   has  a  good perception  (76%) and  positif    attitude   toward  to Agroforward    Auction    Market (76%).  Beside   there   were   significantly relationship  between   their  perception  on  this  market  system  and  their   attitude  toward   to this agroforward auction market system.Key word : agroforward, auction.Market.